PEMBUATAN DAN PENERJEMAHAN MEDIA PROMOSI ‘BIG FARMER’ DI DESA KERTAWANGI, KABUPATEN BANDUNG BARAT - Febryanto, Mohammad; Zewitra, Zewitra; Purnamasari, Yessy; Nugraha, Danny Gandana; Bakhti, Krisna Yudha (Jurnal AbdiMas Nusa Mandiri, 2025)
Kertawangi Village, located in Cisarua District, West Bandung Regency, has great potential as a tourist destination due to its mountainous topography and cool climate. The majority of the village's population relies on agriculture and livestock. The local government has strived to develop the village into an international tourist destination by forming a tourism awareness group (POKDARWIS) and initiated the 'Big Farmer' program in 2020. However, the lack of promotional media in both Indonesian and English hinders the progress of promoting this program as well as the village. This community service program aims to provide bilingual promotional media for Kertawangi Village by creating and translating a program profile and brochure that can be used by POKDARWIS and the local community. The method involved three main stages: planning, implementation, and evaluation. The data was primarily obtained from interviews with POKDARWIS members as well as local residents. The result consists of a bilingual program profile and brochure containing information about the history, vision and mission, core values, activities, products and services, partnerships, markets and customers, as well as the team behind the ‘Big Farmer’ program. The development of these promotional materials may enhance the visibility of Kertawangi Village as a tourist destination, support the local economy's sustainability, and advance community-based tourism.